Genetics of aging and its impact on human longevity: theories and evidences that helps to prevent age-associated diseases - Cruz, Ivana Beatrice Mânica da (2015)
Biogerontological studies about the factors that affect the human longevity and suscessful aging are highly relevant. Therefore, here this paper I review and coment some questions about currently aging theories, the existence (or not) of “longevity genes” and main genetics mechanisms potentially involved in aging and lifespan. From this review I also will consider the impact environment on genetic and epigenetic factors on human aging, health and longevity.